Thought Leadership in Advancing International Business Research - Lewin, Arie Y. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
This volume is devoted to those areas that can advance our understanding of international business. It contains contributions from intellectual leaders of the field, using cutting edge research to explore frontier topics in international business, and to look at where international business is going.